1987
DOI: 10.1002/hlca.19870700120
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of 3,3′‐Oxybis[(diphenylphosphino)methylbenzene] with Ni(II), Pd(II), Pt(II), Rh(I), and Ag(I). How Important is Backbone Rigidity in the Formation of trans‐Spanning Bidenatate Chelates??

Abstract: The bidentate diphosphine ligdnd, 3,3'-oxybis[(dipenylphosphino)methylbenzene] (1) forms monomeric, truns-square-planar complexes MX2(1) (M = Ni, Pd, Pt; X = CI-., Br-, I-, and, in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The Ag atom is three-coordinate with the AgP 2 Cl central coordination unit in a planar configuration. The arrangement of the donor atoms is intermediate between a trigonal planar and T-shaped geometry with P(1)−Ag−P(2) = 145.61(8)° for the more flexible pop ligand and 140.7(1)° for the more rigid L1a ligand . Thus, the less rigid pop ligand prefers larger P(1)−Ag−P(2) bond angles than the flexible L1a ligand.…”
Section: Preformed Ligand Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The Ag atom is three-coordinate with the AgP 2 Cl central coordination unit in a planar configuration. The arrangement of the donor atoms is intermediate between a trigonal planar and T-shaped geometry with P(1)−Ag−P(2) = 145.61(8)° for the more flexible pop ligand and 140.7(1)° for the more rigid L1a ligand . Thus, the less rigid pop ligand prefers larger P(1)−Ag−P(2) bond angles than the flexible L1a ligand.…”
Section: Preformed Ligand Strategymentioning
confidence: 99%
“…To determine the effect of the rigidity of the preformed span, Kapoor and co-workers synthesized the Ag(pop)Cl complex for comparison with Ag(L1a)Cl . The molecular structure of Ag(pop)Cl closely resembles that of Ag(L1a)Cl.…”
Section: Preformed Ligand Strategymentioning
confidence: 99%
“…Mononuclear complexes of Type 5 (Scheme 8) have been obtained for the ligands 2,11-bis(di-R-phosphinomethyl)benzo(c)phenanthrene (R = Ph, X = Cl, SnCl 3 [135]; R = t Bu, X = Cl, Br, ClO 4 [136], Et [137]), 3,3 -oxybis[(diphenylphosphino)methyl]benzene [138], bis(diphenylphosphanyl)-O-carborane [139] and R-[(4-MeC 6 H 4 ) 2 P(C 10 H 6 ) 2 ] 2 [(R)-Tol-Binap] [140].…”
Section: Silver(i) Complexes Of Bidentate Phosphinesmentioning
confidence: 99%
“…Many trans-complexes of ligand 14 have been synthesized as Ni14X 2 (X = Cl, I, NCS, CN), Pd14X 2 (X = Cl, Br, I, ONO, N 3 ), Pt14X 2 (X = Br, I, Cl), Pt14HCl, Pt14HBr, Ag14Cl or Rh14(CO)Cl and fully characterized by spectroscopic techniques [110][111][112][113]. The data analysis suggested that ligand 14 forms exclusively monomeric species in high yields with Ni(II) and Pd(II).…”
Section: General Description Of the Known Ligands: Main Coordination mentioning
confidence: 99%
“…Several studies were also directed to unravel how the increased flexibility of ligand 14 compared to 1 would affect its tendency to form trans-coordinating complexes concluding that it does not have a detrimental effect [109,110]. Many trans-complexes of ligand 14 have been synthesized as Ni14X 2 (X = Cl, I, NCS, CN), Pd14X 2 (X = Cl, Br, I, ONO, N 3 ), Pt14X 2 (X = Br, I, Cl), Pt14HCl, Pt14HBr, Ag14Cl or Rh14(CO)Cl and fully characterized by spectroscopic techniques [110][111][112][113].…”
Section: General Description Of the Known Ligands: Main Coordination mentioning
confidence: 99%